Rheumatic Exercise Activities As A Form Of Rheatoid Arthritis Prevention In Rt 26 Sawah Lebar District, Bengkulu City - Merichi, Tien Novita; Apriyanti, Eva; Andreano, Andreano; Dwi Haikal, Muhammad; Saputra, Rizki; Surahman, Fery (Jurnal Pengabdian Mandiri, 2025)
Based on data from the World Health Organization (WHO) in 2016, approximately 335 million people worldwide suffer from rheumatism (Rasiman, N.B & Reskiani, 2022). According to Riskesdas data from 2018, the prevalence of rheumatism in Indonesia reached 7.30%. The diagnosed prevalence by doctors is higher among women (8.5%) compared to men (6.1%) (Ministry of Health, RI, 2018). The purpose of this study is to improve the health of elderly and pre-elderly individuals who are already affected by rheumatoid arthritis or are at risk of developing the disease. The method used in this research is through Practical Rheumatic Exercise Activities. Results and Discussion: In this community service activity titled "Rheumatic Exercise Activities as a Form of Rheumatoid Arthritis Prevention in Rt. 26, Sawah Lebar Subdistrict, Bengkulu City", the participants agreed to conduct rheumatic exercise sessions for the elderly at least 1-2 times per month. Recommendations: It is hoped that the results of these rheumatic exercise activities can continue to be implemented to promote the health of elderly and pre-elderly individuals who are affected by or at risk of rheumatoid arthritis.